2023
DOI: 10.1038/s41579-023-00852-y
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus host interactions and adaptation

Abstract: Invasive Staphylococcus aureus infections are common, causing high mortality, compounded by the propensity of the bacterium to develop drug resistance. S. aureus is an excellent case study of the potential for a bacterium to be commensal, colonizing, latent or disease-causing; these states defined by the interplay between S. aureus and host. This interplay is multidimensional and evolving, exemplified by the spread of S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
139
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(142 citation statements)
references
References 175 publications
2
139
0
1
Order By: Relevance
“…While a single gene or gene cluster was not found to be indicative of colonisation, our comprehensive genomic analysis demonstrated that MSCRAMM genes frequently exhibited variability in persister strains over time, implying that selection pressure might act on the MSCRAMM genes in chronic colonisation. Interestingly, we found that persisters commonly had both small and structural MSCRAMM gene variants over time, suggesting that once colonisation has occurred, persister strains may attenuate their virulence profiles by adaptive evolution over time (Howden et al, 2023). Detailed analysis of the sdr locus deletion in 4875 revealed recombination of the folding domains from the sdrC gene and the wall-spanning and sort domain of the sdrD gene, suggesting that intra-host surface adhesin modulation can occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a single gene or gene cluster was not found to be indicative of colonisation, our comprehensive genomic analysis demonstrated that MSCRAMM genes frequently exhibited variability in persister strains over time, implying that selection pressure might act on the MSCRAMM genes in chronic colonisation. Interestingly, we found that persisters commonly had both small and structural MSCRAMM gene variants over time, suggesting that once colonisation has occurred, persister strains may attenuate their virulence profiles by adaptive evolution over time (Howden et al, 2023). Detailed analysis of the sdr locus deletion in 4875 revealed recombination of the folding domains from the sdrC gene and the wall-spanning and sort domain of the sdrD gene, suggesting that intra-host surface adhesin modulation can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Pathoadaptation of persistent colonisers in (chronic) inflammatory conditions has been described for pathogens such as S. aureus and Pseudomonas aeruginosa (Howden et al, 2023; Rossi et al, 2021). A surprising finding in this study was the significantly increased biofilm antibiotic tolerance over time of the S. aureus strains that are persistent.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, C5aR1 has been identified to promote bacterial infections, as it can act as a receptor for toxins including those secreted by Staphylococcus aureus ( Spaan et al, 2013 , 2014 , 2015 ; Li et al, 2017 ; Chow et al, 2020 ). S. aureus stably colonizes the skin, noses, and throats of more than 30% of the human population without causing symptoms, but may infect deeper tissues because of catheters, intubation, or immunosuppression ( Thwaites et al, 2011 ; Howden et al, 2023 ). In particular, methicillin-resistant S. aureus strains that express Panton–Valentine leukocidin (PVL) cause severe infections such as necrotizing pneumonia, fasciitis, and sepsis that are increasingly difficult to treat with common antibiotics ( Lee et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To combat the threat posed by neutrophils, S. aureus has evolved numerous mechanisms of evading opsoninic complement and antibody [12,13,14,15]. For example, S. aureus produces two immunoglobulin binding proteins, Spa and Sbi, that reduce antibody-mediated opsonisation, whilst the production of proteins such as SCIN, Efb and CHIPS reduces complement deposition, activation and detection by immune cells [12][13][14][15][16][17][18][19][20][21][22][23][24]. As such, the bacterial cell surface is a critically important determinant in immune detection of S. aureus and efforts by the pathogen to evade surveillance and killing by host defences.…”
Section: Introductionmentioning
confidence: 99%